Air Pollution and Entrepreneurship - Liwen Guo; Zhiming Cheng; Massimiliano Tani; Sarah Cook; Jiaqi Zhao; Xi Chen (Global Labor Organization (GLO), 2022)
We examine the causal effect of air pollution on an individual's propensity for entrepreneurship in China. Our preferred model, which employs an instrumental variable approach to address endogeneity arising from sorting into entrepreneurship and locational choices, suggests that exposure to higher intensity of air pollution lowers one's proclivity for entrepreneurship. A one standard deviation increase in air pollution leads to a 21.2% decrease in the propensity for entrepreneurship. We also find that self-efficacy is a channel in the relationship between air pollution and entrepreneurship. In addition, education moderates the relationship between air pollution and self-efficacy.
Keywords: J24; L26; Q53; 330; Air pollution; Entrepreneurship; China